AN ANALYSIS OF THE PERFORMANCE OF THE AVIATION INDUSTRY IN INDONESIA: IN PANDEMIC PERIOD WITH SERVQUAL METHOD AND IMPORTANCE PERFORMANCE ANALYSIS - Sentosa, Endri; Syafriana Effendi, Maya; Rahma Diana, Shinta (Dinasti Publisher, 2021)
The aviation industry is one of the most globally affected industries by the COVID-19 pandemic. It employs millions of people and supports tens of millions of others, as well as being the nerve center of international business and tourism. The losses of aviation industry will extend to its branches industries. The determination of policies that are not in favor of the industry related to the Avtur VAT, disharmony between ministries has caused the impact of this covid-19 adding heavy burden in industry sector. High operational costs, aircraft leasing, maintenance and others will be higher if the exchange rate also increases. This study aims to determine the analysis of the performance of national aviation industry due to the Covid19 pandemic. The results of this study are expected to be used as input in formulating policies in order to increase economic value in the aviation industry. Method of research which was done, namely comparing literature reviews from journals that discussed airlines with the use of Servqual theory and applied the Importance Performance Analysis method, and the authors made the descriptive analysis. The results of the study showed that covid 19 had a significant impact on the aviation industry, and the results of the performance analysis suggested that in order to survive in Covid-19 condition, the government needed to involve to provide a stimulus to the aviation industry.